Screening for Viruses and Lemur-Associated Filara in Wild-Caught Mosquitoes From Madagascar. Issue 2 (9th October 2020) - Klein, Annette; Strube, Christina; Becker, Stefanie C; Naccache, Fanny
Abstract: Madagascar is a hotspot of biodiversity, but poverty and population growth provoke a high risk of conflict between food security and biodiversity conservation in this tropical country. Numerous vector-borne diseases, including viral infections, affect public health in Madagascar and a continuous expansion of anthropogenically used areas intensifies contact on the human–wildlife interface. However, data on human and animal pathogens in potential insect vectors is limited. Therefore, we conducted a parasitological and virological survey of 785 adult female mosquitoes between March and May 2016 at the Ankarafantsika National Park in northwestern Madagascar. Screening included A lpha-, Phlebo -, and Flaviviridae and the recently described filarial nematode species, Lemurfilaria lemuris . The predominant mosquito genus was Culex (91%), followed by Mansonia (4.1%), Anopheles (3.4%), and Aedes (0.9%). Viral screening revealed no arboviruses, but an insect-specific flavivirus in two Culex sitiens pools. No pools screened positive for the lemur-specific filarial nematode L. lemuris . Graphical Abstract: